Study of the relationship between the chiorophyll and the nitrogen content of oilseed rapes - ZHU Zhe-yan; BAO Yi-dan; HUANG Min; FENG Lei (浙江大学学报. 农业与生命科学版)
In order to fined the relationship between the SPAD value and the nitrogen content of oilseed rapes, a Minolta SPAD-502 Meter was used for on-farm measurement of the N content, and then the Kjeldahl method has been used for measuring the nitrogen content of these oilseed rapes. The results of these two methods have been fitted, as a result, the correlation coefficient is 0.863, a new method for quickly measuring the nitrogen content of oilseed rapes is offered.